A comparison of the efficacy of immunomodulatory-free regimens in relapsed or refractory multiple myeloma: a network meta-analysis. Issue 1 (2nd January 2019) - Weisel, Katja; Sonneveld, Pieter; Spencer, Andrew; Beksac, Meral; Rizzo, Maria; Xu, Yingxin; Fahrbach, Kyle; Gaudig, Maren; Slavcev, Mary; Dearden, Lindsay; Lam, Annette
Abstract: Treatment history influences the outcomes of subsequent therapies in patients with relapsed or refractory multiple myeloma (RRMM) and needs to be considered when deciding which treatment to use next. To assess the relative merits of immunomodulatory (IMiD)-free treatments, a systematic literature review (SLR) was conducted to identify relevant randomized controlled trials in patients with RRMM. A network meta-analysis (NMA) was performed to assess various IMiD-free regimens, including bortezomib and dexamethasone (Vd)–based treatments, and to explore differences in patient outcomes. The SLR identified 52 articles, from which four trials were ultimately included in the base-case NMA. The NMA showed that daratumumab plus Vd (DVd) provided a significant advantage in prolonging progression-free survival. Similar trends were observed for overall survival and overall response. Across all outcomes, DVd had the highest probability of being the best treatment. These findings suggest that DVd may provide superior clinical outcomes for RRMM patients suitable for IMiD-free regimens.